2021
DOI: 10.1186/s12889-021-10859-w
|View full text |Cite
|
Sign up to set email alerts
|

Health issues and healthcare utilization among adults who reported exposure to tear gas during 2020 Portland (OR) protests: a cross-sectional survey

Abstract: Background Repeated use of chemical irritants for crowd-control by local and federal law enforcement during sustained racial justice protests in the U.S. has raised concerns about potential adverse health effects. The objective of this study was to describe the health consequences of exposure to tear gas agents and associated healthcare utilization among adults reporting recent exposure to tear gas. Methods A cross-sectional, self-administered web-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Number of days of exposure had a significant positive associations with experiencing an adverse reproductive health outcome as participants who reported adverse reproductive health outcomes. This finding confirmed our hypothesis and, while the magnitude of each adverse reproductive health outcome was not quantified in this analysis, the significant association and increased days of exposure may indicate a crude dose-response pattern which has been observed for other health outcomes previously in tear gas exposure studies ( 10 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Number of days of exposure had a significant positive associations with experiencing an adverse reproductive health outcome as participants who reported adverse reproductive health outcomes. This finding confirmed our hypothesis and, while the magnitude of each adverse reproductive health outcome was not quantified in this analysis, the significant association and increased days of exposure may indicate a crude dose-response pattern which has been observed for other health outcomes previously in tear gas exposure studies ( 10 ).…”
Section: Resultssupporting
confidence: 91%
“…More recently, evidence of a dose-response relationship between to self-reported tear gas exposure and menstrual irregularities was established in Portland, Oregon utilizing cross-sectional data from summer 2020 exposures ( 10 ). Toxicology studies establishing CS and CN Immediately Dangerous to Life or Health Concentrations (IDLH) were last conducted in military settings in the 1960s and did not include surveillance for reproductive health effects ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Protests occurred over many weeks and federal agents repeatedly deployed massive quantities of chemical irritants and smoke including via thermal foggers, as shown in Figure 1.5 -hand-held devices producing large volumes of tear smoke from water or oil-based solutions, as well as from 'smoke pots' -open pots of burning incandescent substance (believed to be HC -Hexachloroethane) that produced dense clouds of grey/ white smoke. Protesters reported a wide range of respiratory and/or reproductive health impacts after attending protests and being exposed to the chemical irritants, including unusual effects on menstrual cycles (see Torgrimson-Ojerio et al, 2021).…”
Section: Global Contextmentioning
confidence: 99%
“…One peer-reviewed study based on a web-based survey of 2257 adults reporting recent exposure to tear gas in Portland, Oregon (U.S.), found that 54.5% of 1650 respondents who potentially menstruate reported menstrual changes. The most reported issues were increased menstrual cramping, unusual spotting, increased bleeding, and more days of bleeding (Torgrimson-Ojerio et al, 2021).…”
Section: Characteristics and Techniquesmentioning
confidence: 99%
“…Deployment of the tear gas agent 2-chlorobenzalmalononitrile (CS; C 10 H 5 ClN 2 , CAS: 2698-41-1) for riot control has significantly increased in recent years ( Olajos and Salem, 2001 ; Blain, 2003 ; Bessac et al, 2009 ; Bessac and Jordt, 2010 ; Schep et al, 2015 ; Rothenberg et al, 2016 ; Torgrimson-Ojerio et al, 2021 ). CS tear gas has been commonly used by police forces as a riot control agent (RCA) to disperse crowds and subdue individuals.…”
Section: Introductionmentioning
confidence: 99%